Phytochemical and anti-inflammatory properties of selected plants used in preparing Lana. - Dela Cruz, Darwin Tulisar (2008.)
Among the numerous plants used by herbolarios in the preparation of lana, three were analyzed for their phytochemical and anti-inflammatory properties. These are ayo (Casuarina equisetifolia), tagulauai (Parameria laevigata) and kaldemon (Atalantia disticha). The crude methanolic extracts of the three plants were subjected to phytochemical tests for the presence of alkaloids, flavonoids and saponins. Laboratory screening for alkaloids showed that these are present only in kaldemon. Flavonoids were found to be present i ayo, while all three plants were positive in saponins. The extracts of the three plants and locally made coconut oil were evaluated for their anti-inflammatory activities using the Carrageenan-induced edema assay. Coconut oil exhibit the highest anti-inflammatory activity with percent inhibition 0f 61.6%. This is statistically similar to the inhibitory effect of the positive control (Indomethacin) with percent inhibition of 55.3%. The same is true with ayo which showed a percent inhibition of 45.7%. There is a significant difference in the inhibitory effects of coconut oil and ayo, however. Kaldemon and tagalauai exhibited the lowest anti-inflammatory activities with percent inhibitions of 21.5% and 19.6%, respectively.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Lana (Oil); Traditional medicine; Plants -- Anti-infammatory Properties; Plants -- Phytochemical